A Neural Method of Finding Frequent Subgraph Patterns - Li, Changhao. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Computer Science.; Advisor: Liping Liu.; Committee: Xiaozhe Hu, and Donna Slonim.; Keyword: Computer science.